Full‐thickness oesophageal regeneration in pig using a polyurethane mucosal cell seeded graft. (4th June 2017) - Barron, Matthew R.; Blanco, Ellen W.; Aho, Johnathon M.; Chakroff, Jason; Johnson, Jed; Cassivi, Stephen D.; Carey, William A.; Wigle, Dennis A.
Abstract: Malignant oesophageal pathology typically requires resection of a portion of oesophagus. The aim of this study was to investigate attachment and growth of swine oesophageal mucosal cells on electrospun synthetic nanofibre matrices of varying chemistries and to determine whether a mucosal‐seeded graft, in a swine animal model, could induce regeneration. Swine mucosal oesophageal cells were isolated and seeded them onto five different matrix materials. Matrix samples were cultured for up to 14 days, after which matrices were analysed for cell attachment. Attachment varied for each of the matrix materials tested, with the most rigid showing the lowest levels of attachment. Importantly, sections of these matrices illustrated that multiple layers of mucosal cells formed, mimicking endogenous oesophageal structure. A tdTomato reporter line (mucosal tdt cells) was created to enable cell tracking. As polyurethane matrix was found optimal through in vitro testing, a graft was prepared using mucosal tdt cells, along with an unseeded control, and implanted into swine for determination of oesophageal regeneration. Mucosal seeded polyurethane grafts initiated full thickness regeneration of the oesophagus, including epithelial, submucosal, and skeletal muscle layers which were highly vascularized. Interestingly, an unseeded graft showed similar regeneration, indicating that the role of cells in the process of oesophageal regeneration is still unclear. The electrospun polyurethane matrix does appear suitable for multilayered cellular attachment and growth of oesophageal mucosal cells, and implantation of polyurethane grafts initiated full thickness regeneration of the oesophagus, indicating potential for oesophageal reconstruction in humans. Copyright © 2016 John Wiley & Sons, Ltd.